If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(6x + 10) = -8(-4x + 7) Reorder the terms: 4(10 + 6x) = -8(-4x + 7) (10 * 4 + 6x * 4) = -8(-4x + 7) (40 + 24x) = -8(-4x + 7) Reorder the terms: 40 + 24x = -8(7 + -4x) 40 + 24x = (7 * -8 + -4x * -8) 40 + 24x = (-56 + 32x) Solving 40 + 24x = -56 + 32x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-32x' to each side of the equation. 40 + 24x + -32x = -56 + 32x + -32x Combine like terms: 24x + -32x = -8x 40 + -8x = -56 + 32x + -32x Combine like terms: 32x + -32x = 0 40 + -8x = -56 + 0 40 + -8x = -56 Add '-40' to each side of the equation. 40 + -40 + -8x = -56 + -40 Combine like terms: 40 + -40 = 0 0 + -8x = -56 + -40 -8x = -56 + -40 Combine like terms: -56 + -40 = -96 -8x = -96 Divide each side by '-8'. x = 12 Simplifying x = 12
| -3(x-5)=x-13 | | -(1x-2)-6.5=2.5x+19 | | 6x+17=15x-111 | | 2x+8=4(x-3) | | 2v+6=-4(1v+3) | | 4z=-40 | | x+35=84-74 | | 180-x=2(x+20) | | 180x=2(x+20) | | -5.7p+10.16=-65.08 | | x+20=180-2(x+20) | | 2[x+3]=-4[x+1] | | -3b+ax=x-4 | | x+20=180-(x+20) | | 147-3b^2=0 | | (2b^5-5b^4+8b^3-12b^2+12b-9)= | | 15y-16=7y-15 | | 0.2n+3= | | 3(2x+5)=5x+12 | | 7[3-(-4x-1)]=252x+84 | | 10x-8=102 | | 8x-2(x-5)=x+5 | | 31s+10=-14s | | V^2+12v-24=0 | | 6(2t+5)=4 | | -45=-6(-36-4) | | 7n^2-52n-32=0 | | x^2-x=552 | | 20+x=2(20+x) | | (3p-4)=35 | | 2(x-5)+3(2x-8)= | | 16=8 |